Réception du 11 septembre 2001 au Québec. Persistance des mémoires nationales et émergence de mémoires globalisées - Christian Bergeron (Transatlantica)
Everyone (or almost) remembers the fateful date associated with the collapsing Twin Towers of the World Trade Center in New York, the terrorist attacks in Washington and Pennsylvania State. In this article, we study in Quebec the impact and the signification of the September 11, 2011 among different age cohorts. In this way, we would see the importance of the globalization in their historical self. Based on a mixed-methods research design, the study involved 504 adults from Quebec City participated in the CEVI international study (Changes and Events across the Life Course). The quantitative results of socio-historical changes show the importance of the September 11 attacks, reflecting the trends of the globalization of collective memories. This event affected the historical self of many people that we studied and was an occasion to deepen the phenomenon of globalization.